Analysis of Corporate Governance on the Business Operations of the Grain Marketing Board and the Zimbabwe National Water Authority - Titos Mbambi; Dominic Uzhenyu (Journal of Business and Social Review in Emerging Economies)
Purpose: The study sought to analyse how corporate governance was affecting the business operations of Grain Marketing Board (GMB) and the Zimbabwe National Water Authority (ZINWA). These two parastatals have had challenges of corporate governance which has been always an issue for most parastatals largely covered by media reports and research studies.